New potential biomarkers for mesterolone misuse in human urine by liquid chromatography quadrupole time‐of‐flight mass spectrometry. (January 2015) - Lu, Jianghai; Fernández‐Álvarez, María; Yang, Sheng; He, Genye; Xu, Youxuan; Aguilera, Rodigo
<x xml:space="preserve">Abstract</x> In this paper, mesterolone metabolic profiles were investigated carefully. Mesterolone was administered to one healthy male volunteer. Urinary extracts were analyzed by liquid chromatography quadruple time‐of‐flight mass spectrometry (LC‐QTOFMS) for the first time. Liquid–liquid extraction was applied to processing urine samples, and dilute‐shoot analyses of intact metabolites were also presented. In LC‐QTOFMS analysis, chromatographic peaks for potential metabolites were hunt down by using the theoretical [M–H]− as target ions in full scan experiment, and their actual deprotonated ions were analyzed in targeted MS/MS mode. Ten metabolites including seven new sulfate and three glucuronide conjugates were found for mesterolone. Because of no useful fragment ion for structural elucidation, gas chromatography–mass spectrometry instrumentation was employed to obtain structural details of the trimethylsilylated phase I metabolite released after solvolysis. Thus, their potential structures were proposed particularly by a combined MS approach. All the metabolites were also evaluated in terms of how long they could be detected, and S1 (1α‐methyl‐5α‐androst‐3‐one‐17β‐sulfate) together with S2 (1α‐methyl‐5α‐androst‐17‐one‐3β‐sulfate) was detected up to 9 days after oral administration, which could be the new potential biomarkers for mesterolone misuse. Copyright © 2015 John Wiley & Sons, Ltd.